Non-Carcass Parts of Local Male Ducks Fed Commercial Feed Supplemented with Torch Ginger (Etlingera elatior) Flower Extract - Mohammad Badru Zaman; Ristika Handarini; Deden Sudrajat (Talenta Publisher, 2018)
The torch ginger (Etlingera elatior) is a herbaceous plant the flower of which is commonly used in feed to improve the quality of meat. This study was aimed at assessing the effects of giving commercial feed non-carcass portions of local ducks. The study was conducted at the Poultry Farm of Department of Animal Husbandry Djuanda University, Bogor, from June to August 2016. Twenty four 2-week-old male local ducks were used. Completely randomized design with 4 treatments and 3 replicates was used. The treatments consisted of 100% of commercial ration (R0), commercial ration + 2.5% of TGE solution (R1), commercial ration + 5% of TGE solution (R2), and commercial ration + 7.5% of TGE solution (R3). The feeding trial lasted 6 weeks after which the ducks were slaughtered and carcass weight, dressing percentages and carcass parts were measured. The percentage of non-carcass parts including head, neck, shank, liver, heart, gizzard, feathers, blood and intestines were also measured. No significant effect of treatments (P > 0.05) on all parameters measured were found. It was concluded that the inclusion of TGE solution in commercial ration up to 7.5% did not significantly affect the live weight, weight and percentages of non-carcass parts including blood, feathers, head, neck, shank, liver, gizzard, heart, and intestines.